The The Social Disaster Intelligence Paradox in Understanding Bioterrorism - Bhakti, Dahan Cendikia; Syamsunasir Syamsunasir; Anwar Kurniadi; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2024)
World history always has a dark side when it comes to the topic of terrorism, especially the use and research of biological weapons. Even though a number of prohibitions and international agreements have been issued regarding the prohibition of researching, storing and using biological weapons for all countries in the world, there are still many countries in the world that are suspected of secretly carrying out research, storing and using biological weapons for certain purposes in secret. hiding on the basis of accusations/evidence based on speculation, a series of interconnected phenomena, to the discovery of physical evidence related to acts of bioterrorism. So it is interesting to carry out research related to the clarity of understanding regarding the issue of bioterrorism in the modern era, especially from the perspective of social disaster intelligence. This research uses descriptive qualitative methods and a literature study approach. Research results based on the causes of the phenomenon of disease spread are based on conjectures, interpretations and hypotheses about the use of biological weapons as a form of bioterrorism and the lack of specificity in the definition of acts of terrorism itself, creating a confusing paradox between an epidemic disease being a natural phenomenon.